Thermogravimetric analysis (TGA) decomposition and morphological study of Empty Fruit Bunch (EFB) torrefied under N2, O2 and CO2 atmosphere - Srinivasan, Suppulakshmi (IRC, 2016)
Due to biomass essential carbon neutrality, it is environmentally beneficial in using biomass as a renewable energy reserve via presently available thermochemical treatment processes. Torrefaction is known to be a thermal treatment process used in production of high graded solid biofuels from various streams of biomass or agricultural residue. This study uses empty fruit bunch (EFB) as the raw biomass material, in where, EFB is torrefied at 300 °C under N2, O2 and CO2 atmospheres at concentration of 100% N2, 21% O2 (nitrogen balance), 21% CO2 (nitrogen balance), and a mixture of 9% O2 & 12% CO2 (nitrogen balance) and 12% O2 & 9% CO2 (nitrogen balance).